Sensor Device on Lateral Passing Distance : a case study with an unsupervised learning model to estimate hazardous areas for bicycle mobility - Mello, Luiz Marcel Silva de (2023)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Civil e Ambiental, Programa de Pós-Graduação em Transportes, 2023.